The Nazis : a warning from history. Volume 2 (United Kingdom : BBC Worldwide, 2004)
Contents: The wrong war--The wild east.
"2 Titles in each DVD".--Cover.
Keywords: International Baccalaureate; Nazis; World War II; Documentary films; Documentary films